Promotion of Hydrogen Desorption from Palladium Surfaces by Fluoropolymer Coating. Issue 9 (9th April 2016) - Delmelle, Renaud; Ngene, Peter; Dam, Bernard; Bleiner, Davide; Borgschulte, Andreas
Abstract: The catalytic activity of Pd surfaces towards hydrogen desorption was significantly improved by a nanometer‐thin polytetrafluoroethylene (PTFE) layer, as shown by an enhancement in the permeability of a Pd membrane coated on the permeate side. The origin of this effect was found to be due to a lowering of the barrier for hydrogen desorption, as evidenced by a change in the rate‐limiting mechanism of hydrogen permeation through the membrane from desorption (un‐coated) to diffusion controlled. In situ X‐ray photoelectron spectroscopy (XPS) revealed the electronic structure of the sputtered PTFE. Apart from C–F n subunits ( n =1, 2, 3), we found that nonsaturated carbon atoms became hydrogenated during hydrogen permeation, which was indicative of an interaction between Pd and PTFE. This interaction was weak; no Pd−F bonds were formed. We thus attributed the effect to an increase in the hydrophobicity of the surface by the porous PTFE layer and to a promoter effect of hydrogen desorption as a result of electrostatic interactions between chemisorbed hydrogen and physisorbed PTFE. Abstract : Access granted : The permeation kinetics of H2 through a Pd membrane is significantly enhanced by the presence of a polytetrafluoroethylene (PTFE) coating deposited on the permeate side. The H2 flux is increased both in ultrahigh vacuum (UHV) and in air. This is attributed to a combination of the hydrophobicity of PTFE and a promoter effect that enhances the desorption kinetics by the electrostatic field generated by the F atoms present in the coating.